Optical absorption, charge separation and recombination dynamics in Sn/Pb cocktail perovskite solar cells and their relationships to photovoltaic performances. Issue 17 (7th May 2015) - Shen, Qing; Ogomi, Yuhei; Chang, Jin; Toyoda, Taro; Fujiwara, Kosei; Yoshino, Kenji; Sato, Koki; Yamazaki, Kohei; Akimoto, Masaya; Kuga, Yuki; Katayama, Kenji; Hayase, Shuzi
<x xml:space="preserve">Abstract</x> Charge separation and recombination dynamics in Sn/Pb cocktail perovskite solar cells were clarified.